The Effect of Caffeinated Coffee on Tears Secretion among Young Adults: Caffeinated Coffee and Tears Secretion - Sajid, Ayesha; Bilal, Abdullah; Saeed, Sameer; Hamza, Muhammad; Isham, . (Pakistan BioMedical Journal, 2025)
Caffeine, the most often taken psychoactive stimulant, is said to have contradictory effects on tear film dynamics. Objectives: To determine the effect of caffeinated coffee on tears secretion. Methods: Quasi experimental study was conducted from January 2023 to May 2024 at Superior University Lahore including 86 subjects of ages between 18-35 years by using convenient sampling technique. After visual acuity assessment, tear secretion of participants was checked by using Schirmer test strips. Tears secretion of all the subjects was noted before and after intake of caffeinated coffee by using Schirmer test strips. Descriptive statistics and T test was used for analysis of data by using SPSS version 25.0. Results: Before intake of coffee, 14(16.3%) showed tear secretion in the range of 5-15 mm, 21(24.4%) were in range of 16-25mm while 51(59.3%) were in the range of 26-35mm. Tear secretions after 30 minutes of coffee intake in 23(26.7%) subjects were in the range of 5-15mm, 20(23.3%) were in the range of 16-25mm while 43(50%) were in the range of 26-35mm. Similarly tear secretions after 90 minutes of coffee intake in 35(40.7%) were in the range of 5-15mm, 32(37.2%) were in the range of 16-25mm while 19(22.1%) were in the range of 26-35mm. Tear secretions before and after intake of coffee was found to be statistically significant i.e. p<0.05. Conclusion: A decreasing trend was observed in tear secretion levels at 30 and 90 minutes following the intake of caffeinated coffee and normal prior to coffee consumption